The Effectiveness of Digital Applications in Enhancing News Writing Skills - Bramantoro, Ardianto; Suyatno; Urip Zaenal Fanani; Anas Ahmadi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
Language skills consist of four aspects, one of which is writing skills. At the junior high school (SMP) level, one of the writing skills taught is writing news texts. In writing news, it is necessary to pay attention to the elements, structure, and linguistic rules. However, in reality, many students still experience difficulties in composing news texts. These difficulties can stem from various factors, such as a lack of understanding of text structure, limited vocabulary, low interest in reading news, and inadequate ability to express ideas coherently and logically. In addition, the limited use of engaging and relevant learning media also presents a challenge in the writing learning process. Teachers are required to provide innovative and creative instruction in order to achieve the learning objectives. Various models, methods, strategies, and learning media can be used to make this happen. The aim of this study is to determine the effectiveness of digital applications in improving students' ability to write news texts. Digital applications are considered suitable and relevant to be implemented in education in line with current technological developments. The method used in this study is a literature review, which aims to analyze the effectiveness of digital applications in enhancing news writing skills. The results of the literature review indicate that the use of digital applications in learning is effective in increasing students’ interest and motivation to learn. In addition, students’ understanding of the subject matter also improves, as evidenced by the fact that students’ scores are now above average.